Myoma Expulsion after Uterine Artery Embolization - Vivian Fernanda do Amaral; Fernanda Yumi Yochiy; Mário Luiz Furlanetto; Spencer Luiz Marques Payão (Case Reports in Surgery)
Introduction. Uterine leiomyomas are the most common benign pelvic tumors in women over 35 years and can be symptomatic or asymptomatic. Among the main treatment strategies, there are hormone therapy, hysterectomy, myomectomy, and uterine artery embolization (UAE), a recent and promising treatment for patients who wish to avoid hysterectomy. Ideal candidates for UAE are women with symptomatic uterine leiomyomas that present no desire for pregnancy, premenopausal and heavy menstrual bleeding, or dysmenorrhea caused by intramural fibroids. Case Presentation. A 36-year-old female diagnosed with leiomyomas and an extensive history of failed previous treatments who, in order to preserve her uterus, underwent UAE and had tumor expulsion 15 days after the procedure. The patient remained eight months in amenorrhea and, currently, presents normal hormone levels and irregular periods. Conclusion. UAE presents itself as a minimally invasive procedure and as an efficient alternative for those patients who wish to preserve their uteri and also improve their symptoms and quality of life.